Wet pulverization method

CN122935448APending Publication Date: 2026-10-16NIPPON CHEMICAL IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580021495.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-03-05
Filing Date
2025-03-10
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

按照本发明,能够提供一种降低了源自粉碎介质及副生组分的杂质导致的污染的被粉碎材料的湿式粉碎方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a wet pulverization method of a pulverized material, which reduces contamination caused by impurities from a pulverization medium. The wet pulverization method of the present invention is characterized by having: a first step of bringing a dispersion solvent containing a pulverized material into contact with an acid or an acidic compound to obtain a mixed solution for wet pulverization treatment; and a second step of performing wet pulverization treatment of the mixed solution for wet pulverization treatment with a pulverization medium filled in a wet pulverization treatment device to obtain a pulverization-treated wet pulverization treatment solution, the pulverized material being a material that increases the pH of the dispersion solvent when brought into contact with the dispersion solvent, and the pH of the mixed solution for wet pulverization treatment being controlled to be 9 or higher and 11 or lower in the second step to perform the wet pulverization treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a wet pulverization method for materials to be pulverized, wherein the contamination effect of the pulverizing media is reduced. Background Technology

[0002] Perovskite-type composite oxides, represented by barium titanate, have traditionally been used as raw materials for functional ceramics such as piezoelectric elements and multilayer ceramic capacitors. However, in recent years, multilayer ceramic capacitors have required increased layer count and high dielectric constant to achieve high capacitance, necessitating the nano-micronization of perovskite-type composite oxides.

[0003] The micronization of perovskite composite oxides can be achieved through various methods, such as using pulverizers like bead mills, ball mills, and spray mills. Among these, bead mills are frequently used because they use fine grinding beads as the pulverizing medium, which not only applies less force to the perovskite composite oxide powder being pulverized but also results in a higher frequency of collisions with the fine grinding beads. Therefore, bead mills are frequently employed as a method that can achieve micronization while suppressing damage to the particles.

[0004] Several methods have been proposed for pulverizing perovskite-type composite oxides using bead mills. For example, Patent Document 1 describes a method that uses a medium containing silicon nitride-based ceramic materials as the medium for pulverizing barium titanate-based semiconductor ceramic raw materials, which can reduce the content of contaminants caused by medium wear. Patent Document 2 describes a method that uses grinding beads such as Y₂O₃ or SiO₂, which are chemically soluble in acids, to pulverize the material, and then separates the wear powder produced by the grinding beads through acid dissolution treatment, thereby obtaining high-purity pulverized material. Patent Document 3 proposes a method that uses oxide or carbonate particles soluble in acids as grinding beads to pulverize inorganic or organic slurries, and then adds an acidic substance to the slurry to dissolve the grinding beads, thereby avoiding contamination caused by grinding bead components.

[0005] On the one hand, there are methods described in the aforementioned patent documents. On the other hand, methods have also been proposed to prevent contamination of the pulverized material caused by wear of the grinding beads, even if the material being pulverized is not limited to perovskite-type composite oxides. For example, Patent Document 4 describes a technical solution that adjusts the pH of a mixture containing the pulverized material, grinding beads, and dispersion medium to 6.5 to 9, thereby reducing contamination caused by the grinding beads.

[0006] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 7-251086 Patent Document 2: Japanese Patent Application Publication No. 2010-51887 Patent Document 3: Japanese Patent Application Publication No. 2018-58053 Patent Document 4: International Publication No. 2020 / 179701 Summary of the Invention

[0007] The problem that the invention aims to solve The aforementioned patent documents describe a grinding method using a bead mill, which employs grinding beads as the grinding medium. Therefore, various methods are used to remove impurities to prevent the components constituting the grinding beads from becoming contaminated as impurities due to wear on the bead surface. However, contamination of the ground material is still frequently observed, necessitating further research into methods to prevent contamination. Furthermore, the pH value of the mixture containing the ground material can influence the leaching and reaction of components originating from the ground material, leading to their contamination as byproducts.

[0008] Therefore, the object of the present invention is to provide a wet pulverizing method for pulverizing materials that reduces contamination caused by impurities from the pulverizing medium and byproducts.

[0009] Technical solutions for solving the problem After repeated and in-depth research considering the above-mentioned practical situation, the inventors of this invention discovered that: when wet grinding is performed using metal oxides such as zirconium oxide and alumina as grinding media, the collision between the material being ground and the grinding media wears down the surface of the grinding media, leading to metal contamination of the ground material. Furthermore, if the pH value of the dispersion solvent increases, the surface of the grinding media becomes even more susceptible to wear. Moreover, mixing acid or acidic compounds into the wet grinding system, preventing the pH value of the dispersion solvent from becoming too high during wet grinding, inhibits wear on the surface of the grinding media. In addition, it was found that if the pH value of the dispersion solvent decreases, components originating from the ground material will dissolve, causing side reactions and generating impurities, thus leading to a deterioration in the quality of the ground material. Thus, this invention was completed.

[0010] That is, the present invention (1) provides a wet pulverizing method, characterized by having: The first step involves contacting a dispersing solvent containing the material to be pulverized with an acid or acidic compound to obtain a mixture for wet pulverization; and In a wet grinding process device filled with a grinding medium, the mixture for wet grinding is subjected to wet grinding using the grinding medium to obtain a wet grinding liquid after grinding. The pulverized material is one that increases the pH value of the dispersion solvent when in contact with it, and... In the second step described above, the pH value of the wet pulverizing solution is controlled between 9 and 11 for wet pulverizing.

[0011] Furthermore, the present invention (2) provides a wet pulverizing method according to (1), characterized in that, during the process of supplying the wet pulverizing mixture to the wet pulverizing processing apparatus and discharging the wet pulverizing liquid from the wet pulverizing processing apparatus, the wet pulverizing mixture is wet pulverized in the wet pulverizing processing apparatus using the pulverizing medium to obtain a wet pulverizing liquid after pulverization, thereby performing the second step described above.

[0012] Furthermore, the present invention (3) provides a wet pulverizing method according to (2), characterized in that the residence time of the wet pulverizing mixture in the pulverizing process of the second step is 1 to 1200 seconds.

[0013] Furthermore, the present invention (4) provides a wet pulverizing method according to any one of (1) to (3), characterized in that the following process is repeated more than once: the wet pulverizing liquid obtained in the second step is brought into contact with an acid or an acidic compound to obtain a wet pulverizing mixture, thereby performing the first step; then, the obtained wet pulverizing mixture is subjected to wet pulverizing treatment, thereby performing the second step.

[0014] Furthermore, the present invention (5) provides a wet pulverizing method according to any one of (1) to (4), characterized in that, in the first step described above, a dispersing solvent containing the material to be pulverized is brought into contact with an acid or acidic compound, thereby reducing the pH value of the dispersing solvent containing the material to be pulverized by 0.10 to 5, and obtaining a mixture for wet pulverizing treatment.

[0015] Furthermore, the present invention (6) provides a wet pulverizing method according to any one of (1) to (5), characterized in that the pH value of the wet pulverizing treatment liquid obtained by performing the second step is above 9 and below 11.

[0016] Furthermore, the present invention (7) provides a wet pulverizing method according to any one of (1) to (6), characterized in that the acid or acidic compound is selected from one or more of inorganic acids, organic acids and acidic dispersants.

[0017] Furthermore, the present invention (8) provides a wet pulverizing method according to (7), characterized in that the inorganic acid is selected from one or more of carbonic acid, hydrochloric acid, nitric acid and sulfuric acid.

[0018] Furthermore, the present invention (9) provides a wet pulverizing method according to (7), characterized in that the organic acid is selected from one or more of formic acid, acetic acid, citric acid, succinic acid and malonic acid.

[0019] Furthermore, the present invention (10) provides a wet pulverizing method according to (7), characterized in that the above-mentioned acidic dispersant is one or two selected from polycarboxylic acid compounds, polyphosphoric acid compounds and phosphonic acid compounds.

[0020] Furthermore, the present invention (11) provides a wet grinding method according to any one of (1) to (10), characterized in that the grinding medium is one or more grinding beads or grinding balls selected from zirconium oxide, alumina, silicon dioxide, titanium dioxide and silicon nitride.

[0021] Furthermore, the present invention (12) provides a wet pulverizing method according to any one of (1) to (11), characterized in that the dispersing solvent is water or a mixture of water and an aqueous organic solvent.

[0022] Furthermore, the present invention (13) provides a wet pulverization method according to any one of (1) to (12), characterized in that the material to be pulverized is a perovskite-type composite oxide.

[0023] Furthermore, the present invention (14) provides a wet pulverization method according to (13), characterized in that the perovskite-type composite oxide is selected from one or more of barium titanate, calcium titanate, magnesium titanate, strontium titanate, barium calcium titanate, barium strontium titanate, barium magnesium titanate, calcium magnesium titanate, and magnesium strontium titanate.

[0024] Furthermore, the present invention (15) provides a wet pulverizing method according to any one of (1) to (14), characterized in that the content of the pulverized material in the dispersion solvent containing the pulverized material is 5 to 80% by mass.

[0025] Furthermore, the present invention (16) provides a wet pulverizing method according to any one of (1) to (15), characterized in that the volume ratio of the pulverizing medium to the wet pulverizing mixture is 10 to 90 by volume.

[0026] Invention Effects According to the present invention, a wet pulverizing method for pulverized materials can be provided, which reduces contamination caused by impurities originating from the pulverizing medium and byproducts. Detailed Implementation

[0027] The wet pulverizing method of the present invention is characterized by having: The first step involves contacting a dispersing solvent containing the material to be pulverized with an acid or acidic compound to obtain a mixture for wet pulverization; and In a wet grinding process device filled with a grinding medium, the mixture for wet grinding is subjected to wet grinding using the grinding medium to obtain a wet grinding liquid after grinding. The pulverized material is one that increases the pH value of the dispersion solvent when in contact with it, and... In the second step described above, the pH value of the wet pulverizing solution is controlled between 9 and 11 for wet pulverizing.

[0028] The first step of the wet pulverization method for the material to be pulverized according to the present invention is to contact a dispersing solvent containing the material to be pulverized with an acid or acidic compound to obtain a mixture for wet pulverization treatment.

[0029] The dispersing solvent in the wet pulverization method for the material to be pulverized according to the present invention is not particularly limited, as long as it can uniformly and finely pulverize the material to be pulverized by the pulverizing medium. Examples of suitable solvents include water or a mixture of water and an aqueous organic solvent. Examples of suitable water include pure water, ion-exchanged water, tap water, and industrial water. Pure water and ion-exchanged water are preferred, and pure water is particularly preferred, from the perspective of preventing contamination of the material to be pulverized. Examples of suitable aqueous organic solvents include methanol, ethanol, propanol, butanol, ethylene glycol, and toluene. Ethanol is particularly preferred from the perspective of ease of operation and more uniform fine pulverization of the material to be pulverized. It should be noted that the water content in the mixture of water and the aqueous organic solvent is preferably 50% by mass or more.

[0030] In the wet grinding method of the present invention, the material to be ground is a material whose pH value is increased by contacting a dispersing solvent such as water or a mixture of water and an aqueous organic solvent. When wet grinding is performed using metal oxides such as zirconium oxide or alumina as the grinding medium, an increase in the pH value of the dispersing solvent makes the surface of the grinding medium more susceptible to wear. Therefore, in the wet grinding method of the present invention, since the object of wet grinding is a material whose pH value increases upon contact with the dispersing solvent, an acid or acidic compound is mixed into the wet grinding system before the grinding process to prevent the pH value of the dispersing solvent from becoming too high during the wet grinding process.

[0031] As the wet pulverization method for the pulverized material of the present invention, perovskite-type composite oxides can be cited as examples of pulverized materials. Perovskite-type composite oxides are compounds whose pH value increases upon contact with water or a mixture of water and an aqueous organic solvent, which serves as a dispersion solvent. There are no particular limitations on perovskite-type composite oxides, as long as they have an ABO3-type structure. However, perovskite-type composite oxides with at least one element selected from Ba, Ca, Mg, and Sr at the A-site and at least one element selected from Ti, Sn, Pb, and Zr at the B-site are preferred. Examples of perovskite-type composite oxides in which the A-site element is selected from at least one of Ba, Ca, Mg, and Sr, and the B-site element is selected from at least one of Ti, Sn, Pb, and Zr, include barium titanate, calcium titanate, magnesium titanate, strontium titanate, barium calcium titanate, barium magnesium titanate, barium strontium titanate, calcium magnesium titanate, calcium strontium titanate, magnesium strontium titanate, barium stannate, calcium stannate, magnesium stannate, strontium stannate, barium calcium stannate, barium magnesium stannate, barium strontium stannate, calcium magnesium stannate, calcium strontium stannate, magnesium strontium stannate, barium zirconate, calcium zirconate, and zirconium. Magnesium zirconate, strontium zirconate, barium calcium zirconate, barium magnesium zirconate, barium strontium zirconate, calcium magnesium zirconate, calcium strontium zirconate, magnesium strontium zirconate, barium stannate titanate, calcium stannate titanate, magnesium stannate titanate, strontium stannate titanate, barium calcium stannate titanate, barium magnesium stannate titanate, barium strontium stannate titanate, calcium magnesium stannate titanate, calcium strontium stannate titanate, magnesium strontium stannate titanate, barium zirconate titanate, calcium zirconate titanate, magnesium zirconate titanate, strontium zirconate titanate, barium calcium zirconate titanate, barium magnesium zirconate titanate, barium magnesium zirconate titanate, barium strontium zirconate titanate, barium magnesium zirconate titanate, barium strontium zirconate titanate, calcium magnesium zirconate titanate, calcium strontium zirconate titanate, magnesium strontium zirconate titanate, etc.

[0032] The average particle size of the perovskite-type composite oxide used as the pulverized material is preferably 0.010–1 μm, more preferably 0.020–0.5 μm. This average particle size within the above range is preferred because it is readily available and easy to process. It should be noted that, in this invention, the average particle size of the perovskite-type composite oxide used as the pulverized material refers to the BET-converted particle size, which is the particle size calculated from the specific surface area measured by the BET method, assuming the particles are spherical.

[0033] The preferred BET specific surface area of ​​the perovskite-type composite oxide used as the pulverized material is 0.10 m². 2 / g or more, more preferably 0.5 to 50 m 2 / g. The BET specific surface area of ​​this perovskite-type composite oxide is within the above range, and it is preferred because it is readily available and easy to process.

[0034] The preparation method for the perovskite-type composite oxide that becomes the pulverized material is not specific; for example, organic acid salt methods such as the oxalate method, co-precipitation methods, hydrolysis methods, hydrothermal synthesis methods, and solid-state methods can be used. Furthermore, commercially available perovskite-type composite oxides can also be used as the perovskite-type composite oxide forming the pulverized material.

[0035] Perovskite-type composite oxides obtained by organic acid salt methods—particularly oxalate methods or solid-phase methods—dissolve a large amount of alkali (A-site) components from the particle surface upon contact with the dispersing solvent, water, or a mixture of water and an aqueous organic solvent. This increases the pH value of the dispersing solvent upon contact. Therefore, when the material being pulverized is a perovskite-type composite oxide obtained by organic acid salt methods—particularly oxalate methods or solid-phase methods—contact with the dispersing solvent causes the pH value of the dispersing solvent to become excessively high, necessitating the use of acids or acidic compounds to lower the pH value of the dispersing solvent. Therefore, from the perspective of achieving more significant effects in this invention, perovskite-type composite oxides obtained by organic acid salt methods such as oxalate methods or solid-phase methods are preferred as the perovskite-type composite oxides forming the pulverized material.

[0036] Furthermore, perovskite-type composite oxides obtained by hydrolysis or hydrothermal synthesis exhibit a lower increase in pH of the dispersion solvent even when in contact with water or a mixture of water and an aqueous organic solvent, due to the smaller amount of alkali (A-site) components dissolved from the particle surface. However, even when the material to be pulverized is a perovskite-type composite oxide obtained by hydrolysis or hydrothermal synthesis, the pH of the dispersion solvent can still become too high if the pulverization time is prolonged or the number of pulverization cycles is increased. Therefore, it is necessary to use an acid or acidic compound to lower the pH of the dispersion solvent. Thus, even when the perovskite-type composite oxide used as the material to be pulverized is obtained by hydrolysis or hydrothermal synthesis, and the pH of the dispersion solvent has become too high due to pulverization conditions and repeated pulverization, the effects of the present invention can still be achieved by implementing the first and second steps of the wet pulverization method for the material to be pulverized according to the present invention.

[0037] The acid used in the wet pulverization method of the material to be pulverized according to the present invention can be an inorganic acid or an organic acid. As an inorganic acid, it is preferably selected from one or more of carbonic acid, hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and hydrofluoric acid. It should be noted that when carbonic acid is used as the inorganic acid, carbon dioxide is introduced into the dispersion solvent containing the material to be pulverized to generate carbonic acid in the dispersion solvent, allowing the carbonic acid to contact with the dispersion solvent containing the material to be pulverized. As an organic acid, it is preferably selected from one or more of formic acid, acetic acid, citric acid, succinic acid, and malonic acid. Furthermore, as an acidic compound used in the wet pulverization method of the material to be pulverized according to the present invention, an acidic dispersant can be cited as an example. An acidic compound refers to a dispersion solvent that, upon contact with water or a mixture of water and an aqueous organic solvent, generates H+ in the dispersion solvent. ﹢ Compounds. Examples of acidic dispersants include polycarboxylic acid compounds, polyphosphoric acid compounds, and phosphonic acid compounds. Among these, from the perspective of further suppressing contamination caused by impurities from the grinding medium in the second process, the acid or acidic compound is preferably carbonic acid, hydrochloric acid, nitric acid, or acetic acid.

[0038] Furthermore, in the first step of the wet pulverization method for the material to be pulverized according to the present invention, the dispersing solvent containing the material to be pulverized is contacted with an acid or acidic compound to obtain a mixture for wet pulverization. Examples of methods for contacting the dispersing solvent containing the material to be pulverized with an acid or acidic compound include: adding an aqueous solution of an acid to the dispersing solvent containing the material to be pulverized and mixing; introducing carbon dioxide into the dispersing solvent containing the material to generate carbonic acid, thereby bringing the carbonic acid into contact with the dispersing solvent; and adding a dispersion of an acidic compound to the dispersing solvent containing the material to be pulverized and mixing. Since the material to be pulverized is a material whose pH value increases upon contact with the dispersing solvent, in the first step, the dispersing solvent containing the material to be pulverized is contacted with an acid or acidic compound to lower the pH value of the dispersing solvent.

[0039] As a dispersing solvent containing the pulverized material, an example is a dispersing solvent prepared by mixing the pulverized material, which has not undergone pulverization, into the dispersing solvent. Alternatively, the wet pulverization treatment liquid obtained in the second step can also be used as a dispersing solvent containing the pulverized material.

[0040] The content of the pulverized material in the dispersing solvent containing the pulverized material is preferably 5 to 80% by mass, more preferably 10 to 70% by mass. A content of the pulverized material in the dispersing solvent within the above range improves pulverization efficiency, thereby increasing yield, resulting in uniform particle size, and producing high-quality particles.

[0041] When the material to be pulverized is a perovskite-type composite oxide, upon contact with water or a mixture of water and an aqueous organic solvent, the A-site element dissolves into the dispersion solvent, increasing the pH value of the dispersion solvent to, for example, a pH value exceeding 11, indicating strong alkalinity. The inventors of this invention have discovered that when the material to be pulverized is pulverized using a pulverizing medium while the pH value of the wet pulverization mixture is maintained at a high level, the pulverizing medium dissolves into the dispersion solvent, causing contamination of the micro-pulverized perovskite-type composite oxide by impurities from the pulverizing medium. Furthermore, the inventors of this invention have also discovered that if the pH value of the wet pulverization mixture is too low, impurity byproducts from the dissolved A-site element are easily generated, leading to contamination of the micro-pulverized perovskite-type composite oxide. Therefore, in the first step, by contacting an acid or acidic compound with a dispersion solvent containing the material to be pulverized (which increases the pH value of the dispersion solvent through contact with the dispersion solvent), a wet pulverization mixture containing the material to be pulverized can be obtained where the pH value of the dispersion solvent is controlled between 9 and 11. That is, in the first step, an acid or acidic compound is brought into contact with a dispersion solvent containing the material to be pulverized, which increases the pH value of the dispersion solvent by contact with the dispersion solvent, so that a wet pulverization mixture with the pH value controlled within the optimal range can be obtained.

[0042] In the first step, it is preferable to contact the dispersing solvent containing the material to be pulverized with an acid or acidic compound, thereby lowering the pH value of the dispersing solvent containing the material to be pulverized by 0.10 to 5, particularly by 0.50 to 4, to obtain a wet pulverizing mixture. Since a wet pulverizing mixture with the pH value of the dispersing solvent containing the material to be pulverized reduced within the above-mentioned range is obtained, the effect of preventing leaching of the pulverizing medium and contamination caused by byproducts in the second step is improved.

[0043] In the first step, the pH value of the wet grinding mixture obtained by contacting an acid or acidic compound with a dispersing solvent containing the material to be ground is 9 or higher and 11 or lower. The lower limit of the pH range of the wet grinding mixture is 9 or higher, preferably higher than 9, more preferably 9.1 or higher, further preferably higher than 9.1, particularly preferably 9.2 or higher, and most preferably higher than 9.2; the upper limit is 11 or lower, preferably lower than 11, and more preferably 10.9 or lower. These upper and lower limits can be combined. If the pH value of the wet grinding mixture is lower than 9, impurity byproducts originating from A-site elements are easily generated, leading to contamination of the micro-ground perovskite-type composite oxide; while if the pH value exceeds 11, the grinding medium will dissolve into the dispersing solvent, and the micro-ground perovskite-type composite oxide will be contaminated by impurities originating from the grinding medium. When the pH value of the wet grinding mixture is within the above-mentioned range, not only can wear on the surface of the grinding medium be suppressed during wet grinding, but the effect of reducing impurities originating from A-site elements is also improved.

[0044] In the first step, for example, by contacting a dispersion solvent containing the material to be pulverized with an acid or acidic compound at a pH of 11 or higher, preferably 12 or higher, a wet pulverizing mixture can be obtained with a pH value controlled at 9 or higher and lower than the pH value before mixing with the acid or acidic compound, preferably with a pH value controlled at higher than 9 and lower than 11.

[0045] In the first step, when preparing a dispersion solvent containing pulverized material by mixing the uncrushed material into a dispersion solvent, for example, the dispersion solvent can be added to a mixing container first, and then the pH value of the dispersion solvent can be monitored. Under the condition that the amount of pulverized material mixed with the dispersion solvent and the amount of acid or acidic compound (in the case of introducing carbon dioxide into the dispersion solvent for contact with carbonic acid, the amount of carbon dioxide introduced into the dispersion solvent) are controlled, the uncrushed material and acid or acidic compound are continuously or intermittently contacted with the dispersion solvent, and the pH value of the dispersion solvent is maintained near the target pH value to carry out the first step, thus preparing a mixture for wet pulverization.

[0046] Furthermore, when a wet pulverizing solution obtained in the second step is used as a dispersing solvent containing the material to be pulverized in the first step for multiple wet pulverization processes, for example, while introducing the wet pulverizing solution obtained in the second step into a mixing container, the pH value of the dispersing solvent is monitored. Under the condition of controlling the output of the wet pulverizing solution obtained in the second step and the amount of acid or acidic compound mixed (in the case of introducing carbon dioxide into the dispersing solvent for contact with carbonic acid, it is the amount of carbon dioxide introduced into the dispersing solvent) the wet pulverizing solution obtained in the second step and the acid or acidic compound are continuously or intermittently introduced into the mixing container, so that the pH value of the dispersing solvent is maintained near the target pH value, thereby preparing a wet pulverizing solution.

[0047] The wet pulverizing mixture obtained from the first step is a product of dispersing the pulverized material in a dispersion solvent whose pH value has been adjusted with an acid or acidic compound. In other words, the wet pulverizing mixture obtained from the first step contains the pulverized material and is dispersed in a dispersion solvent whose pH value has been adjusted with an acid or acidic compound.

[0048] The second step of the wet pulverization method for the material to be pulverized according to the present invention is to perform wet pulverization treatment on the wet pulverization treatment mixture obtained in the first step using a pulverizing medium to obtain a wet pulverization treatment liquid after pulverization treatment.

[0049] In the second step, the wet grinding mixture is introduced into a grinding device filled with grinding media. The wet grinding mixture is mixed and stirred with the grinding media, thereby performing wet grinding treatment on the wet grinding mixture containing the material to be ground.

[0050] The wet grinding apparatus involved in the wet grinding method for the material to be ground according to the present invention is not particularly limited, as long as it is an apparatus capable of stirring the liquid within the wet grinding apparatus—that is, the material to be ground, the dispersing solvent, and the grinding medium—to allow the material to be ground, the dispersing solvent, and the grinding medium to flow. In the wet grinding method for the material to be ground according to the present invention, examples of wet grinding apparatuses that grind the material to be ground while stirring the material to be ground, the dispersing solvent, and the grinding medium include, for example, bead mill apparatuses and ball mill apparatuses.

[0051] The pulverizing medium used in the wet pulverizing method of the present invention is not particularly limited, as long as it can uniformly micronize the material and facilitate separation from the pulverized material. For example, it is preferably selected from one or more of zirconium oxide, alumina, silicon dioxide, titanium dioxide, and silicon nitride. In addition, from the perspective of effectively micronizing the material, the shape of the pulverizing medium is preferably granular, such as bead-shaped or spherical.

[0052] In the second step, when grinding beads are used as the grinding medium, the diameter of the grinding beads is preferably 0.005 to 10.0 mm, and particularly preferably 0.01 to 6.0 mm. When grinding balls are used as the grinding medium, the diameter of the grinding balls is preferably 0.05 to 20 mm, and particularly preferably 0.1 to 10 mm.

[0053] In the second step, although the stirring speed for agitating the wet grinding mixture and grinding media within the wet grinding apparatus depends on the size of the grinding apparatus, it is preferably 2 to 14 m / s in terms of circumferential speed, and particularly preferably 3 to 13 m / s, at a scale of 0.1 L. When the stirring speed for agitating the wet grinding mixture and grinding media within the wet grinding apparatus is within the above range, the grinding media moving in the wet grinding mixture can effectively grind the material being ground.

[0054] In the second step, when the wet grinding treatment mixture and grinding media are stirred in the wet grinding treatment device, the stirring conditions are as follows: in the case of a wet grinding treatment device used as a bead mill, for example, the volume ratio of the grinding media to the wet grinding treatment mixture is preferably 10 to 90% by volume, particularly preferably 20 to 80% by volume; and the stirring speed, in terms of circumferential speed, is preferably 2 to 14 m / s, particularly preferably 3 to 13 m / s.

[0055] In the second step, the temperature during the pulverization of the material in the wet pulverizing device is preferably 5 to 60°C, and particularly preferably 10 to 50°C, when it is desired to obtain fine perovskite-type composite oxides.

[0056] In the second step, the pH value of the wet grinding solution obtained by wet grinding with the grinding medium is preferably 9 or higher and 11 or lower, more preferably greater than 9 and less than 11, and particularly preferably 9.1 or higher and 10.9 or lower. When the pH value of the wet grinding solution is within the above range, the dissolution of the grinding medium and by-products originating from the A-site element can be further suppressed, thereby preventing contamination caused by impurities. It should be noted that the pH value of the wet grinding solution obtained in the second step can be adjusted by, for example, by selecting appropriate wet grinding conditions such as grinding time, residence time, and stirring speed, or by selecting the pH value of the wet grinding mixture before grinding.

[0057] After wet grinding in the second process, the grinding medium is separated from the wet grinding liquid containing the grinding medium by filtering, etc., to obtain the wet grinding liquid.

[0058] The wet pulverization process using the wet pulverization method of the present invention can be performed multiple times as needed. That is, the wet pulverization solution obtained in the second step can be used as the dispersion solvent containing the pulverized material in the first step, and the first and second steps can be repeated at least once, preferably 1 to 1000 times, more preferably 2 to 100 times. Since the pulverization process in the second step creates a new surface on the pulverized material, the pH value of the wet pulverization mixture will increase compared to the pH value of the dispersion solvent containing the pulverized material before the pulverization process. Furthermore, for example, if the second step is performed only for a long time or multiple times in order to form pulverized material of the target particle size, the pH value of the wet pulverization mixture may become excessively high. Therefore, the wet pulverizing mixture obtained in the second step is used as the dispersion solvent containing the pulverized material in the first step. The dispersion solvent containing the pulverized material is then brought into contact with an acid or acidic compound to obtain a wet pulverizing mixture with a lower pH value. In the second step, the wet pulverizing mixture is subjected to wet pulverizing treatment again using a pulverizing medium to obtain a pulverized wet pulverizing solution. Even if the above process is repeated more than once and multiple wet pulverizing treatments are performed, the increase in pH value of the wet pulverizing solution can still be suppressed, further suppressing the dissolution of the pulverizing medium into the wet pulverizing solution and preventing contamination caused by the pulverizing medium.

[0059] In the wet pulverization method of the material to be pulverized according to the present invention, by drying, centrifuging, filtering, etc., the wet pulverization liquid obtained by performing the second step (referring to the last second step when the first step and the second step are repeated multiple times) can be separated and dispersed to obtain the pulverized powder that has undergone wet pulverization treatment as the target product.

[0060] As one embodiment of the wet pulverizing method of the present invention (hereinafter referred to as embodiment (1) of the wet pulverizing method of the present invention), a method can be described in which, in the second step of the wet pulverizing method of the present invention, a wet pulverizing mixture is supplied to a wet pulverizing processing device and a wet pulverizing liquid is discharged from the wet pulverizing processing device, and a wet pulverizing processing liquid is wet pulverized in the wet pulverizing processing device using a pulverizing medium to obtain a pulverized wet pulverizing processing liquid.

[0061] The wet pulverizing method of the present invention, in embodiment (1), is characterized by having: The first step involves contacting a dispersing solvent containing the material to be pulverized with an acid or acidic compound to obtain a mixture for wet pulverization; and In a wet grinding process involving a grinding medium, a mixture for wet grinding is supplied to and discharged from the wet grinding process unit. During this process, the mixture is wet-ground using the grinding medium within the unit to obtain a processed wet grinding solution. The pulverized material is one that increases the pH value of the dispersion solvent when in contact with it, and In the second step described above, the pH value of the wet pulverizing solution is controlled between 9 and 11 for wet pulverizing.

[0062] An embodiment (1) of the wet grinding method of the present invention can be exemplified by a method in which a wet grinding mixture is wet-grinded using a grinding medium in a wet grinding apparatus during the process of supplying a wet grinding mixture from one end of a wet grinding apparatus such as a bead mill and discharging the wet grinding mixture from the other end of the wet grinding apparatus to obtain a wet grinding mixture that has undergone grinding treatment. It should be noted that the shape of the wet grinding apparatus is not particularly limited and can be vertical or horizontal.

[0063] In the second step of the wet pulverizing method of the present invention (1), the residence time of the wet pulverizing mixture is 1 to 1200 seconds, preferably 2 to 900 seconds. It should be noted that the residence time of the wet pulverizing mixture refers to the value obtained by dividing the volume (L) of the wet pulverizing mixture present in the wet pulverizing apparatus during the wet pulverizing process by the supply amount (L / second) of the wet pulverizing mixture supplied to the wet pulverizing apparatus per unit time.

[0064] In embodiment (1) of the wet pulverizing method of the present invention, the target product can be obtained by using the unpulverized material to be pulverized and performing the first and second processes once.

[0065] Furthermore, in embodiment (1) of the wet pulverizing method of the present invention, the following process is repeated more than once to obtain the target wet pulverized product (multi-stage processing): an acid or acidic compound is contacted with the wet pulverizing solution obtained in the second stage to obtain a wet pulverizing mixture, thereby performing the first stage again; then, the obtained wet pulverizing mixture is subjected to wet pulverizing treatment, thereby performing the second stage again. In embodiment (1) of the wet pulverizing method of the present invention, by performing multiple first and second stages, even if multiple wet pulverizing treatments are performed, the pH value of the wet pulverizing solution can be controlled within the range of 9 or higher and 11 or lower, more preferably greater than 9 and less than 11, and particularly preferably 9.1 or higher and 10.9 or lower, further suppressing the dissolution of the pulverizing medium into the wet pulverizing solution and by-products originating from the A-site element, preventing contamination caused by impurities.

[0066] In the wet pulverization method for the material to be pulverized according to the present invention, the average particle size of the pulverized material obtained by BET-converted particle size, such as perovskite-type composite oxides, is preferably 0.005 to 0.9 μm, more preferably 0.01 to 0.4 μm. Furthermore, by appropriately selecting pulverization conditions such as the mixing ratio of the material to be pulverized and the dispersing solvent, the volume ratio of the pulverizing medium to the wet pulverization mixture, the degree of pH adjustment after the addition of acid or acidic compound, and the stirring speed, the BET specific surface area can be made to reach 1.1 to 200 m². 2 / g, preferably 2.5~100 m 2 / g.

[0067] When manufacturing, for example, a multilayer ceramic capacitor, a perovskite-type composite oxide obtained by the wet pulverization method of the material to be pulverized according to the present invention is used, the powder of the perovskite-type composite oxide is first mixed and dispersed in a suitable solvent with conventionally known additives, organic binders, plasticizers, dispersants, etc., including by-product elements, to form a slurry, which is then sheet-formed. This yields a ceramic sheet that can be used in the manufacture of a multilayer ceramic capacitor. When manufacturing a multilayer ceramic capacitor from this ceramic sheet, a conductive paste for forming internal electrodes is first printed on one surface of the ceramic sheet. After drying, multiple sheets of the above-mentioned ceramic sheet are stacked and pressed together along the thickness direction to form a multilayer body. Next, the multilayer body is heat-treated to remove the binder, and then calcined to obtain a calcined body. Further, Ni paste, Ag paste, nickel alloy paste, copper paste, copper alloy paste, etc., are coated onto the calcined body and fired to obtain a multilayer ceramic capacitor.

[0068] Furthermore, when the powder of the perovskite-type composite oxide obtained by the wet pulverization method of the material to be pulverized according to the present invention is combined with resins such as epoxy resin, polyester resin, and polyimide resin to produce resin sheets, resin films, adhesives, etc., in addition to being used as materials for printed circuit boards, multilayer printed circuit boards, etc., it can also be used as a common material for suppressing the shrinkage difference between the internal electrode and the dielectric layer, electrode ceramic circuit board, glass ceramic circuit board, circuit peripheral material, and dielectric material for inorganic EL.

[0069] Furthermore, the perovskite-type composite oxide obtained by the wet pulverization method of the material to be pulverized according to the present invention is suitable for use as a catalyst in reactions such as exhaust gas removal and chemical synthesis, as well as a surface modifier for printing toners that provides antistatic and cleaning effects.

[0070] Example The present invention will be described in more detail below through examples, but the present invention is not limited to these examples. It should be noted that the characteristics in the examples were measured by the following methods.

[0071] (1) Zirconium oxide (ZrO2) content Measurements were performed using an ICAP6000 from Thermo Fisher Scientific via inductively coupled plasma optical emission spectrometry (ICP-OES).

[0072] (2) Average particle size The average particle size will be determined by the cumulative 50% (D50) value of the volumetric frequency particle size distribution, measured by laser diffraction scattering using the MT3300EX laser manufactured by Microtrac Bell.

[0073] (3) BET specific surface area It is obtained through the BET method.

[0074] (4) Alkaline earth metal salt content Measurements were performed using a Bruker D8 ADVANCE via X-ray diffraction (XRD).

[0075] [Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-2] 75 g of barium titanate with an average particle size of 40 nm was added to 300 g of pure water and stirred to prepare a 20% by mass slurry. The pH of this slurry was 13. The slurry was stirred in a jacketed mixing tank at 10°C, and carbon dioxide gas was introduced to control the pH of the slurry to the values ​​shown in Table 1. It should be noted that comparative examples 1-2 did not involve the addition of carbon dioxide gas.

[0076] The resulting slurry was wet-milled using a wet mill (Star Mill LMZ, manufactured by Ashizawa Seiko Co., Ltd.) loaded with 136.80 g of 0.05 mm zirconia grinding beads (equivalent to 40% of the container volume). The milling was carried out at a paddle circumferential speed of 11 m / sec and a slurry flow rate of 50 ml / min. One pass was defined as the process of returning the milled slurry to the jacketed mixing tank and then feeding it back into the wet mill. This process was repeated for a total of 15 passes. Specifically, carbon dioxide gas was introduced into the slurry after each pass to maintain the pH value as shown in Table 1, and this wet milling process was repeated 15 times.

[0077] The pulverized slurry was dried using a dryer at 120℃ to obtain dried powder. The ZrO2 content, average particle size, BET specific surface area, and alkaline earth metal salt (barium carbonate) content of the obtained dried powder are shown in Table 1.

[0078] [Table 1] In Table 1, BT refers to barium titanate.

[0079] As shown in Table 1, the barium titanate powders of each embodiment obtained by adding carbon dioxide to control the pH value of the slurry to be above 9 and below 11 had a lower barium carbonate content in the dried powder compared to Comparative Example 1-1, which was adjusted to a pH value less than 9. Furthermore, it can be seen that the barium titanate powders of each embodiment had a lower ZrO2 content in the dried powder compared to Comparative Example 1-2, which did not undergo pH adjustment and had a slurry pH value greater than 11.

[0080] [Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-2] 75 g of barium titanate with an average particle size of 200 nm was added to 300 g of pure water and stirred to prepare a 20% by mass mixed slurry. The pH of this slurry was 13. The slurry was stirred in a jacketed mixing tank at 10°C, and carbon dioxide gas was introduced to control the pH of the slurry to the values ​​shown in Table 2. It should be noted that Comparative Example 2-2 did not involve the addition of carbon dioxide gas.

[0081] The resulting slurry was wet-milled using a wet mill (Star Mill LMZ, manufactured by Ashizawa Seiko Co., Ltd.) loaded with 136.80 g of 0.05 mm zirconia grinding beads (equivalent to 40% of the container volume). The milling was carried out at a paddle circumferential speed of 11 m / sec and a slurry flow rate of 50 ml / min. One pass was defined as the process of returning the milled slurry to the jacketed mixing tank and then feeding it back into the wet mill. This process was repeated for a total of 15 passes. Specifically, carbon dioxide gas was introduced into the slurry after each pass to maintain the pH value as shown in Table 2, and the wet milling process was repeated 15 times.

[0082] The pulverized slurry was dried using a dryer at 120℃ to obtain dried powder. The ZrO2 content, average particle size, BET specific surface area, and alkaline earth metal salt (barium carbonate) content of the obtained dried powder are shown in Table 2.

[0083] [Table 2] In Table 2, BT refers to barium titanate.

[0084] As shown in Table 2, the barium titanate powders of each embodiment obtained by adding carbon dioxide to control the pH value of the slurry to be above 9 and below 11 had a lower barium carbonate content in the dried powder compared to Comparative Example 2-1, which was adjusted to a pH value less than 9. Furthermore, it can be seen that the barium titanate powders of each embodiment had a lower ZrO2 content in the dried powder compared to Comparative Example 2-2, which did not undergo pH adjustment and had a slurry pH value greater than 11.

[0085] [Examples 3-1 to 3-3 and Comparative Examples 3-1 to 3-2] 75 g of strontium titanate with an average particle size of 40 nm was added to 300 g of pure water and stirred to prepare a 20% by mass slurry. The pH of this slurry was 12. The slurry was stirred in a jacketed mixing tank at 10°C, and carbon dioxide gas was introduced to control the pH of the slurry to the values ​​shown in Table 3. It should be noted that Comparative Example 3-2 did not involve the addition of carbon dioxide gas.

[0086] The resulting slurry was wet-milled using a wet mill (Star Mill LMZ, manufactured by Ashizawa Seiko Co., Ltd.) loaded with 136.80 g of 0.05 mm zirconia grinding beads (equivalent to 40% of the container volume). The milling was carried out at a paddle circumferential speed of 11 m / sec and a slurry flow rate of 50 ml / min. One pass was defined as the process of returning the milled slurry to the jacketed mixing tank and then feeding it back into the wet mill. This process was repeated for a total of 15 passes. Specifically, carbon dioxide gas was introduced into the slurry after each pass to maintain the pH value as shown in Table 3, and this wet milling process was repeated 15 times.

[0087] The pulverized slurry was dried using a dryer at 120℃ to obtain dried powder. The ZrO2 content, average particle size, BET specific surface area, and alkaline earth metal salt (strontium carbonate) content of the obtained dried powder are shown in Table 3.

[0088] [Table 3] In Table 3, ST refers to strontium titanate.

[0089] As shown in Table 3, the strontium titanate powders of each embodiment obtained by adding carbon dioxide to control the slurry pH value to above 9 and below 11 had a lower barium carbonate content in the dried powder compared to Comparative Example 3-1, which had its pH value adjusted to less than 9. Furthermore, it can be seen that the strontium titanate powders of each embodiment had a lower ZrO2 content in the dried powder compared to Comparative Example 3-2, which did not undergo pH adjustment and had a slurry pH value greater than 11.

[0090] [Examples 4-1 to 4-3 and Comparative Examples 4-1 to 4-2] 75 g of strontium barium titanate with an average particle size of 40 nm was added to 300 g of pure water and stirred to prepare a 20% by mass slurry. The pH of this slurry was 12. The slurry was stirred in a jacketed mixing tank at 10°C, and carbon dioxide gas was introduced to control the pH of the slurry to the values ​​shown in Table 4. It should be noted that Comparative Example 4-2 did not involve the addition of carbon dioxide gas.

[0091] The resulting slurry was wet-milled using a wet mill (Star Mill LMZ, manufactured by Ashizawa Seiko Co., Ltd.) loaded with 136.80 g of 0.05 mm zirconia grinding beads (equivalent to 40% of the container volume). The milling was carried out at a paddle circumferential speed of 11 m / sec and a slurry flow rate of 50 ml / min. One pass was defined as the process of returning the milled slurry to the jacketed mixing tank and then re-feeding it into the wet mill. This process was repeated for a total of 15 passes. Specifically, carbon dioxide gas was introduced into the slurry after each pass to control the pH value of the slurry to the values ​​shown in Table 4, and the resulting slurry was wet-milled again. This process was repeated 15 times.

[0092] The pulverized slurry was dried using a dryer at 120℃ to obtain dried powder. The ZrO2 content, average particle size, BET specific surface area, and alkaline earth metal salt (barium carbonate) content of the obtained dried powder are shown in Table 4.

[0093] [Table 4] In Table 4, BST refers to barium strontium titanate.

[0094] As shown in Table 4, the barium strontium titanate powders of each embodiment, obtained by adding carbon dioxide to control the pH value of the slurry to be above 9 and below 11, had a lower content of barium strontium carbonate in the dried powder compared to Comparative Example 4-1, which was adjusted to a pH value less than 9. Furthermore, it can be seen that the barium strontium titanate powders of each embodiment had a lower ZrO2 content in the dried powder compared to Comparative Example 4-2, which did not undergo pH adjustment and had a slurry pH value greater than 11.

[0095] [Examples 5-1 to 5-3 and Comparative Examples 5-1 to 5-2] 75 g of barium calcium titanate with an average particle size of 60 nm was added to 300 g of pure water and stirred to prepare a 20% by mass slurry. The pH of this slurry was 12. The slurry was stirred in a jacketed mixing tank at 10°C, and carbon dioxide gas was introduced to control the pH of the slurry to the values ​​shown in Table 5. It should be noted that Comparative Example 5-2 did not involve the addition of carbon dioxide gas.

[0096] The resulting slurry was wet-milled using a wet mill (Star Mill LMZ, manufactured by Ashizawa Seiko Co., Ltd.) loaded with 136.80 g of 0.05 mm zirconia grinding beads (equivalent to 40% of the container volume). The milling was carried out at a paddle circumferential speed of 11 m / sec and a slurry flow rate of 50 ml / min. One pass was defined as the process of returning the milled slurry to the jacketed mixing tank and then feeding it back into the wet mill. This process was repeated for a total of 15 passes. Specifically, carbon dioxide gas was introduced into the slurry after each pass to maintain the pH value as shown in Table 5, and this wet milling process was repeated 15 times.

[0097] The pulverized slurry was dried using a dryer at 120℃ to obtain dried powder. The ZrO2 content, average particle size, BET specific surface area, and alkaline earth metal salt (barium carbonate) content of the obtained dried powder are shown in Table 5.

[0098] [Table 5] In Table 5, BCT refers to barium calcium titanate.

[0099] As shown in Table 5, the barium calcium titanate powders of each embodiment, obtained by adding carbon dioxide to control the pH value of the slurry to be above 9 and below 11, have a lower content of barium calcium carbonate in the dried powder compared to Comparative Example 5-1, which was adjusted to a pH value less than 9. Furthermore, it can be seen that the barium calcium titanate powders of each embodiment have a lower ZrO2 content in the dried powder compared to Comparative Example 5-2, which did not undergo pH adjustment and had a slurry pH value greater than 11.

[0100] [Examples 6-1 to 6-15] 75 g of barium titanate with an average particle size of 40 nm was added to 300 g of pure water and stirred to prepare a 20% by mass mixed slurry. The pH of this slurry was 13. The slurry was stirred in a jacketed mixing tank at 10°C, and the pH of the slurry was adjusted to the pH value shown in Table 6 while carbon dioxide gas was introduced.

[0101] The resulting slurry was wet-milled using a wet mill (Star Mill LMZ, manufactured by Ashizawa Seiko Co., Ltd.) loaded with 136.80 g of 0.05 mm zirconia grinding beads (equivalent to 40% of the container volume). The milling was carried out at a paddle circumferential speed of 11 m / sec and a slurry flow rate of 50 ml / min. One pass was defined as the process of returning the milled slurry to the jacketed mixing tank and then re-feeding it into the wet mill. This process was repeated for a total of 15 passes. Specifically, the pH of the slurry was controlled at the pH values ​​shown in Table 6 by adding the acids listed in Table 6 after each milling, and this wet milling process was repeated 15 times.

[0102] The pulverized slurry was dried using a dryer at 120℃ to obtain dried powder. The ZrO2 content, average particle size, and BET specific surface area of ​​the obtained dried powder are shown in Table 6.

[0103] [Table 6] In Table 6, BT refers to barium titanate.

[0104] As shown in Table 6, when the pH value of barium titanate powder is controlled to be above 9 and below 11 by adding the acid shown in Table 6, the ZrO2 content in the dried powder is controlled at a low level, and the contamination from the pulverizing medium is suppressed.

Claims

1. A wet pulverizing method, characterized in that, It comprises: a first step of contacting a dispersing solvent containing the material to be pulverized with an acid or acidic compound to obtain a mixture for wet pulverization; and In a wet grinding process device filled with a grinding medium, the mixture for wet grinding is subjected to wet grinding using the grinding medium to obtain a wet grinding liquid after grinding. The pulverized material is one that increases the pH value of the dispersion solvent when in contact with it, and... In the second step, the pH value of the wet pulverizing mixture is controlled between 9 and 11 for wet pulverizing.

2. The wet pulverizing method as described in claim 1, characterized in that, During the process of supplying the wet grinding treatment mixture to the wet grinding treatment device and discharging the wet grinding treatment liquid from the wet grinding treatment device, the wet grinding treatment mixture is wet-grinded using the grinding medium in the wet grinding treatment device to obtain a wet grinding treatment liquid that has undergone grinding treatment, thereby proceeding to the second step.

3. The wet pulverizing method as described in claim 2, characterized in that, The residence time of the wet grinding mixture in the second step of the grinding process is 1 to 1200 seconds.

4. The wet pulverizing method as described in claim 1, characterized in that, The following process is repeated at least once: the wet pulverizing solution obtained in the second step is brought into contact with an acid or acidic compound to obtain a wet pulverizing mixture, thereby performing the first step; then, the resulting wet pulverizing mixture is subjected to wet pulverizing treatment, thereby performing the second step.

5. The wet pulverizing method as described in claim 1 or 2, characterized in that, In the first step, the dispersing solvent containing the material to be pulverized is brought into contact with an acid or acidic compound to reduce the pH value of the dispersing solvent containing the material to be pulverized by 0.10 to 5, thereby obtaining a mixture for wet pulverization.

6. The wet pulverizing method as described in claim 1 or 2, characterized in that, The pH value of the wet pulverizing solution obtained from the second step is above 9 and below 11.

7. The wet pulverizing method as described in claim 1 or 2, characterized in that, The acid or acidic compound is selected from one or more of inorganic acids, organic acids, and acidic dispersants.

8. The wet pulverizing method as described in claim 7, characterized in that, The inorganic acid is selected from one or more of carbonic acid, hydrochloric acid, nitric acid and sulfuric acid.

9. The wet pulverizing method as described in claim 7, characterized in that, The organic acid is selected from one or more of formic acid, acetic acid, citric acid, succinic acid and malonic acid.

10. The wet pulverizing method as described in claim 7, characterized in that, The acidic dispersant is selected from one or two of polycarboxylic acid compounds, polyphosphoric acid compounds, and phosphonic acid compounds.

11. The wet pulverizing method as described in claim 1 or 2, characterized in that, The grinding medium is one or more grinding beads or grinding balls selected from zirconium oxide, alumina, silicon dioxide, titanium dioxide and silicon nitride.

12. The wet pulverizing method as described in claim 1 or 2, characterized in that, The dispersing solvent is water or a mixture of water and an aqueous organic solvent.

13. The wet pulverizing method as described in claim 1 or 2, characterized in that, The material being pulverized is a perovskite-type composite oxide.

14. The wet pulverizing method as described in claim 13, characterized in that, The perovskite-type composite oxide is selected from one or more of barium titanate, calcium titanate, magnesium titanate, strontium titanate, barium calcium titanate, barium strontium titanate, barium magnesium titanate, calcium magnesium titanate, and magnesium strontium titanate.

15. The wet pulverizing method as described in claim 1 or 2, characterized in that, The content of the pulverized material in the dispersion solvent containing the pulverized material is 5-80% by mass.

16. The wet pulverizing method as described in claim 1 or 2, characterized in that, The volume ratio of the pulverizing medium to the wet pulverizing mixture is 10 to 90 by volume.

Citation Information

Patent Citations

  • Medium for kneading and pulverizing semiconductor ceramic raw material

    JP1995251086A

  • Method of manufacturing ultrafine particle powder

    JP2010051887A

  • Dispersion method and pulverization method for slurry middle grains

    JP2018058053A

  • Contaminant-depleted nanoparticle composition and method for producing same

    WO2020179701A1